(untitled) (London Journal of Engineering Research, 2022)
Soil erosion is a severe and uninterrupted problem threatens environment all over the world. Sedimentation has a great effect on basins with large surface areas. Lake Tana basin is one of these lake basins with a surface area of about 15935 km2 . The main objective of this study was to assess soil erosion and concentration of sediment yield of lake Tana basin and map their spatial distribution. The study was conducted by integrating Geographic Information System (GIS), remote sensing and the Revised Universal Soil Loss equation (RUSLE). Data sets of rainfall, soil, topography, cover management and conservation practices were integrated and modelled in GIS. Soil loss, sediment delivery ratio (SDR) and sediment yield were estimated. The results showed that the computed mean annual soil loss was 79.3 t.ha- 1 .y-1 . Six classes of soil erosion were classified: very low (0-5), low (5-10), moderate (10-15), moderately high (15-20), high (20-40) and very high (>40) t.ha-1 .y-1 . About 57.5% of the study area is under low erosion risk (0-10 t.ha-1 .y-1) whereas about 40.3% of the study area is under high and very high erosion risk. SDR was estimated, based on the main stream slope, and found to be 0.281. The findings of the study also showed that the average annual sediment yield of lake Tana basin is approximately 22.28 t.ha-1 .y-1. The results of this study can benefit policy makers to investigate erosional risk areas and to take the best appropriate decisions to control soil erosion risk in these regions.